2014
DOI: 10.1366/13-07210
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Omega-3 Fatty Acids in Fish Oil Supplements Using Vibrational Spectroscopy and Chemometric Methods

Abstract: The potential of Fourier transform infrared (FT-IR), near-infrared (NIR), and Raman spectroscopic techniques combined with partial least squares (PLS) regression (PLSR) to predict concentrations of eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), and total omega-3 fatty acids (n-3 FAs) in fish oil supplements was investigated. FT-IR spectroscopy predicted EPA (coefficient of determination (R(2)) of 0.994, standard error of cross-validation (SECV) of 2.90%, and standard error of prediction (SEP) of 2.49… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 59 publications
4
49
0
Order By: Relevance
“…Also stretching ester carbonyl (-C = O) at 1745 cm −1 and several bands at 1376 cm −1 , 915 cm −1 and 718 cm −1 were observed which were related to finger print region between 1500 and 650 cm −1 can be identified in fish oil spectrum. [20] CSM band at 1420 cm −1 and CS peak at 1077 cm −1 were obvious in CSM/CS hydrogel, showing existence of CSM and CS in fabricated sample. While as shown in spectrum of CSM/CS hydrogel, the peaks at 1620 cm −1 and 1590 cm −1 of CSM and CS were not observed and a new peak at 1553 cm −1 could be detected.…”
Section: Response Surface Optimizationmentioning
confidence: 89%
“…Also stretching ester carbonyl (-C = O) at 1745 cm −1 and several bands at 1376 cm −1 , 915 cm −1 and 718 cm −1 were observed which were related to finger print region between 1500 and 650 cm −1 can be identified in fish oil spectrum. [20] CSM band at 1420 cm −1 and CS peak at 1077 cm −1 were obvious in CSM/CS hydrogel, showing existence of CSM and CS in fabricated sample. While as shown in spectrum of CSM/CS hydrogel, the peaks at 1620 cm −1 and 1590 cm −1 of CSM and CS were not observed and a new peak at 1553 cm −1 could be detected.…”
Section: Response Surface Optimizationmentioning
confidence: 89%
“…Second derivatives of the recorded spectra were calculated in order to improve the resolution of the peaks, at the cost of reduced signal-to-noise ratio, and remove baseline offsets and linear gradients induced by the appearance of water as a reaction product (Verdine and Nakanishi, 1985;Kohler et al, 2007). Additionally, some studies have found that the second derivative reduces the prediction error of the calibration (Bekhit et al, 2014), though Igne et al (2010) suggest its usefulness is dependent on the individual FTIR equipment. The second derivatives in this study were calculated using a 7-point normalised moving average (equation 2)…”
Section: Ftir Calibrationmentioning
confidence: 99%
“…Floriano Ribeiro, Peralta-Zamora, Pereira Ramos, and Pereira-Netto (2013) used mid and near infrared reflectance spectroscopy, with multivariate calibration, to predict LA and ALA content in flax seeds and flax seed flours. Cozzolino, Murray, Chree, and Scaife (2005) employed near infrared (NIR) spectroscopy with partial least squares (PLS) for the determination of FFA in fish oil and, Bekhit, Grung, and Mjøs (2014) investigated the potential of FT-IR, NIR and Raman spectroscopy, with PLS regression models to predict concentrations of EPA, DHA and omega-3 in fish oil supplements. Karlsdottir, Arason, Kristinsson, and Sveinsdottir (2014) evaluated the feasibility of using NIR spectroscopy to determine lipid composition of two lean fish species, hoki and saithe, namely total lipid content, phospholipid, PUFAs and MUFAs.…”
Section: Introductionmentioning
confidence: 99%